2010
DOI: 10.1007/s00213-010-2091-5
|View full text |Cite
|
Sign up to set email alerts
|

Asenapine improves phencyclidine-induced object recognition deficits in the rat: evidence for engagement of a dopamine D1 receptor mechanism

Abstract: These results demonstrate a role for D(1) but not 5-HT(1A) receptor mechanisms in mediating the cognitive effects of asenapine in this rodent model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…It has been suggested that an increase in dopamine release may constitute one possible mechanism for reversing PCP-induced impairments. Consistent with this hypothesis, the putative novel antipsychotic asenapine rescued a PCP-induced deficit with a 1-min delay; the rescue effect could be blocked by a D1 antagonist but not by a 5-HT1A antagonist (Snigdha et al 2010). Asenapine has been shown to increase mPFC and hippocampal dopamine release (Huang et al 2008;Franberg et al 2009).…”
Section: Phencyclidine (Pcp)mentioning
confidence: 78%
See 1 more Smart Citation
“…It has been suggested that an increase in dopamine release may constitute one possible mechanism for reversing PCP-induced impairments. Consistent with this hypothesis, the putative novel antipsychotic asenapine rescued a PCP-induced deficit with a 1-min delay; the rescue effect could be blocked by a D1 antagonist but not by a 5-HT1A antagonist (Snigdha et al 2010). Asenapine has been shown to increase mPFC and hippocampal dopamine release (Huang et al 2008;Franberg et al 2009).…”
Section: Phencyclidine (Pcp)mentioning
confidence: 78%
“…PCP induces robust deficits in SOR with delays as short as 1 min (Grayson et al 2007;McLean et al 2009;Snigdha et al 2010;Sood et al 2010;Damgaard et al 2011;Arnt et al 2010) (but see Hashimoto et al 2005). This does mean, however, that effects on memory versus those on perceptual or motivational factors can be difficult to disentangle.…”
Section: Phencyclidine (Pcp)mentioning
confidence: 89%
“…Indeed, NOR has been listed by the TURNS initiative as relevant for studying visual learning and memory deficits in schizophrenia (TURNS.ucla.edu) and may be used to study cognitive deficits occurring in a range of disorders (Grayson et al, 2014). In our laboratory, we have extensively shown that sub-chronic phencyclidine (PCP) treatment impairs object recognition memory following a 1 min inter-trial interval-ITI (Damgaard et al, 2010(Damgaard et al, , 2011Grayson et al, 2007;Idris et al, 2010;McLean et al, 2009McLean et al, , 2011bSnigdha et al, 2010Snigdha et al, , 2011. We have also demonstrated the efficacy of a wide range of selective receptor targets to reverse these sub-chronic PCP-induced deficits (see for review) as have other labs using the same paradigm (see Meltzer et al, 2013 for review).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of atypical antipsychotics tested, such as clozapine, sertindole, asenapine, olanzapine, melperone, lurasidone and amisulpiride, but not sulpiride, aripiprazole or the typical antipsychotic haloperidol, reversed the impairment in the retention phase of the NOR test subsequent to cessation of the scPCP treatment (Grayson et al 2007;Idris et al 2010;Redrobe et al 2010;Snigdha et al 2010;Horiguchi et al 2011a, b;Snigdha et al 2011;Meltzer 2012, 2013;Maeda et al 2014). Findings from risperidone were less consistent: it was found to reverse the scPCP-induced deficit in the NOR task in female rats (Grayson et al 2007;Snigdha et al 2010;, but failed to reverse it in male rats after acute or repeated administration when a longer intertrial interval (1 h) was used (McKibben et al 2010;Redrobe et al 2010).…”
Section: Pharmacological Validation Of Scpcp Impaired Object Recognitmentioning
confidence: 97%
“…McLean et al 2009a;Arnt et al 2010;Damgaard et al 2010;Idris et al 2010;Damgaard et al 2011;McLean et al 2011;Snigdha et al 2011;Grayson et al 2014), in female LongEvans rats Horiguchi et al 2011a, b;, in male Lister Hooded rats(McKibben et al 2010) and in ovariectomized female Sprague-Dawley rats…”
mentioning
confidence: 98%